Sex-specific associations between maternal prenatal inflammation and offspring cortical morphology in youth: A harmonised study across four birth cohorts - Niskanen, Anni; Barron, Aaron; Azaryah, Hatim; Kerkelä, Martta; Pulli, Elmo; Tuulari, Jetro J.; Lukkarinen, Minna; Karlsson, Linnea; Muetzel, Ryan L.; Campoy, Cristina; Catena, Andrés; Tiemeier, Henning; et al. (Elsevier BV, 2025)
Maternal immune activation (MIA) during pregnancy is implicated in offspring psychiatric disorders. However, it is unknown to what extent MIA affects neurodevelopment, particularly cerebrocortical anatomy, in the general population, and whether effects differ by sex. The current study used vertex-wise statistics to examine the association between maternal prenatal CRP, an archetypal systemic inflammatory marker, and offspring cortical thickness, surface area, and volume, in 2635 mother–child dyads (5.4–26.5 years) from three population-based cohorts, and one clinical cohort enriched for presence of inflammation markers. Maternal CRP within a normal physiological range (<10 mg/L) exhibited sex-specific quadratic associations with cortical morphological measures in 2 regions in males and 1 region in females at childhood. Elevated (>10 mg/L) CRP was associated with regional cortical morphology in females and in a pooled sample of sexes. Overall, MIA is associated with cortical development in a regional and sex-specific manner in studies spanning childhood to adulthood.